Gymnastic Training of Hippotherapy Horses Benefits Gait Quality When Ridden by Riders with Different Body Weights - de Oliveira, Kátia [UNESP]; Clayton, Hilary M.; dos Santos Harada, Érik [UNESP] (Elsevier, 2020)
The objective was to evaluate the effects of gymnastic training on stride characteristics of walk and trot in therapy horses carrying riders of different weights. Eighteen horses used for therapeutic riding 5 days/week were randomly divided into 2 groups. Nine horses performed gymnastic (GYM) exercises after therapeutic riding on 4 days/week for 3 months, 9 horses did no additional exercises (SED). On days 0 and 90, an inertial sensor mounted to the girth on the ventral midline was used to evaluate stride characteristics when horses were ridden at walk (1.3 m/second) and trot (3.0 m/second) by able-bodied riders representing rider: horse body weight ratios (BWRs) 15%, 20%, and 25%. On day 0, the measured variables did not differ significantly between sedentary (SED) and GYM groups, but on day 90, the following statistically significant results were found: GYM-trained horses had higher regularity for all BWRs at walk and 15% and 20% BWRs at trot. Higher stride symmetry was found in GYM-trained horses carrying 25% BWRs at walk and all rider weights at trot. Dorsoventral displacement was higher in GYM-trained horses when carrying 20% and 25% BWRs at walk and 25% BWRs at trot. Dorsoventral power was lower in SED-trained versus GYM-trained horses carrying 15% BWR at walk and 20% BWR at trot. A more regular and symmetrical stride with a larger range of dorsoventral trunk motion is likely to provide a better therapeutic riding experience.
Keywords: Core training; Dynamic mobilization; Equine; Kinematic; Kinetic; Rider weight